Knockdown of NANOG Reduces Cell Proliferation and Induces G0/G1 Cell Cycle Arrest in Human Adipose Stem Cells - Pitrone, Maria (Int J Mol Sci, 2019)
The core components of regenerative medicine are stem cells with high self-renewal and tissue regeneration potentials. Adult stem cells can be obtained from many organs and tissues. NANOG, SOX2 and OCT4 represent the core regulatory network that suppresses differentiation-associated genes, maintaining the pluripotency of mesenchymal stem cells. The roles of NANOG in maintaining self-renewal and undifferentiated status of adult stem cells are still not perfectly established. In this study we define the effects of downregulation of NANOG in maintaining self-renewal and undifferentiated state in mesenchymal stem cells (MSCs) derived from subcutaneous adipose tissue (hASCs). hASCs were expanded and transfected in vitro with short hairpin Lentivirus targeting NANOG. Gene suppressions were achieved at both transcript and proteome levels. The effect of NANOG knockdown on proliferation after 10 passages and on the cell cycle was evaluated by proliferation assay, colony forming unit (CFU), qRT-PCR and cell cycle analysis by flow-cytometry. Moreover, NANOG involvement in differentiation ability was evaluated. We report that downregulation of NANOG revealed a decrease in the proliferation and differentiation rate, inducing cell cycle arrest by increasing p27/CDKN1B (Cyclin-dependent kinase inhibitor 1B) and p21/CDKN1A (Cyclin-dependent kinase inhibitor 1A) through p53 and regulate DLK1/PREF1. Furthermore, NANOG induced downregulation of DNMT1, a major DNA methyltransferase responsible for maintaining methylation status during DNA replication probably involved in cell cycle regulation. Our study confirms that NANOG regulates the complex transcription network of plasticity of the cells, inducing cell cycle arrest and reducing differentiation potential.